A New Sale Document of the Ur III Period in the Sulaymaniyah Museum - Kamil, Ari (Altorientalische Forschungen, 2017)
This contribution presents a copy, transliteration and translation of a Neo-Sumerian cuneiform tablet from the Ur III administration. The document comes from Umma and is kept in the Archaeological Museum of as-Sulaimānīyah (Iraqi Kurdistan).